Coronavirus HKU 1 infection with bronchiolitis, pericardial effusion and acute respiratory failure in obese adult female. (3rd August 2021) - Bianchi, Francesco; Bennett, David; Alderighi, Lorenzo; Pieroni, Maria; Refini, Rosa Metella; Fossi, Antonella; Bargagli, Elena; Mazzei, Maria Antonietta; Guazzi, Gianni; Cusi, Maria Grazia; Sestini, Piersante
Abstract: Seven species of coronavirus cause acute respiratory illness in humans. Coronavirus HKU 1 (CoV HKU 1) was first described in 2005 in an adult patient with pneumonia in Hong Kong. Although it is a well-known respiratory tract pathogen, there is not much information about its role in hospitalized adults, especially in southern Europe. Here, we describe a case of radiologically demonstrated CoV HKU 1-related bronchiolitis with acute respiratory failure in an adult female without significant comorbidities except obesity.